Estatinas, drogas de amplio espectro de acción y beneficios - Arocha-Rodulfo, Ildefonzo (Revista Hospital Clínico Universidad de Chile, 2019)
Prevention and treatment of dyslipidemia should therefore be considered as an integral part of individual cardiovascular prevention interventions, which should be addressed primarily to those at higher risk who will benefit most. Statins are the most commonly used options for the pharmacologic treatment of dyslipidemia. In recent decades, numerous clinical trials have demonstrated the efficacy of these drugs to reduce cardiovascular mortality and major non-fatal atherothrombotic events in heterogeneous populations through both primary and secondary prevention. This group of drugs is part of the recommendations of both US and European guidelines, and should be prescribed to all patients who have already had a cardiovascular event and have no specific contraindication. However, a large percentage of patients that would benefit from a statin treatment do not receive them, have been prescribed a low dose or for a limited time.